Factor-augmenting technical change: An empirical assessment - Enrica De Cian; Carlo Carraro (Fondazione Eni Enrico Mattei (FEEM), 2009)
Starting from a system of factor demands, an empirical model that allows estimating factor-augmenting technical change is derived. Factor-augmenting technical change is defined as the improvement in factor productivities that can occur either exogenously or endogenously, with changes in other macroeconomic variables. This paper provides additional estimates for the substitution possibilities among inputs and it offers new empirical evidence on the direction and sources of factor-augmenting technical change, an issue that has not yet been explored by the empirical literature on growth determinants. The empirical findings suggest that technical change is directed. Technical change tends to be more energy-saving than capital- and labour-saving. Both R&D investments and international trade are important determinants of growth in energy and capital productivity whereas technical change for labour is positively related to education expenditure. Therefore, the sources of factor-augmenting technical change go beyond R&D investments, as proposed in the theory of directed technical change, and they differ across inputs. In other words, not only is technical change directed, the sources of factor-augmenting technical change appear to be input specific.
Keywords: C3; O47; Q55; Q56; 330; Factor-Augmenting Technical Change; Technology Spillovers; Panel Data